AT ANALISIS TEKNIK KEMITRAAN DALAM MENINGKATKAN KEPERCAYAAN MASYARKAT UNTUK ZAKAT, INFAK DAN SEDEKAH PADA LEMBAGA AMIL ZAKAT: ANALISIS TEKNIK KEMITRAAN DALAM MENINGKATKAN KEPERCAYAAN MASYARKAT UNTUK ZAKAT, INFAK DAN SEDEKAH PADA LEMBAGA AMIL ZAKAT - Latif, Ahmad; Budiman; Hidayat, Deden; Daryono, Setyabudi (STAI La Tansa Mashiro, 2024)
The phenomenon that occurs in the institution is a symptom that can be observed, the establishment of an amil zakat institution in the midst of the community is a positive thing and helps the community in distributing zakat funds, infak and alms to the community around the hususnya mustahik (beneficiaries). By using techniques that have been prepared by the institution. technique is an effort or way to achieve an organizational goal by setting a goal long-term and allocate the necessary resources and pay attention to all possibilities that occur and prepare for all the potential that exists, therefore the author analyzes fundraising with partnership techniques that become the author's title in an effort to increase muzzaki trust in order to increase public interest in LAZ Harfa (amil zakat harapan dhuafa institution). In this study, the author has objectives, including to analyze the application of fundraising with the LAZ Harfa partnership technique and to find out the increase in public trust and interest in zakat, infak and alms in the amil zakat institution (LAZ Harfa). The research methodology used in this study is to use a qualitative approach to school action. Then from the data and data sources that have been obtained using observation techniques, observations, interviews and documentation are analyzed in depth by prioritizing the case material findings. Furthermore, from the findings material to find out the questions that exist in the background of the problem. The results of his research are, (1) the application of partnership technology applied based on ritail from personal, MSMEs, health, majlis ta'lim, schools / campuses and communities. (2) The increase in public trust has proven to increase from 2018 there were 728 partners who joined, in 2021 the partners who joined increased to as many as 3292 partners with a percentage of 85.4% which is also proven in the increase in ZIS funds collected in 2018 amounting to Rp 1,236,319,371. and experienced a significant increase in 2021 of 83.5% with a total set of Rp.2,269,504,006, it is proven that with the partnership technique applied by LAZ Harfa, it is very influential on increasing public trust for zakat, infak and alms in institutions. Keywords: Partnership Technique, Trust, Zakat, Amil Zakat Institution